'Mimicking' the West? Russia's legitimization discourse from Georgia war to the annexation of Crimea. Issue 4 (December 2019) - Rotaru, Vasile
Abstract: The 2008 Georgia war represented a turning point in Russian foreign policy. It was for the first time since the dissolution of the Soviet Union when Moscow invaded an independent country and for the first time when two members of the Council of Europe fought against each other. A premiere for Russian post-Soviet foreign policy was registered in 2014 too. The annexation of Crimea represented the first incorporation of foreign territories by Moscow since World War II. These two events generated the West's protest and blatantly contradict Russia's proclaimed foreign policy discourse centered around the respect for states' sovereignty and equality of actors in the international system. Starting from the assertion that the formulation of Russia's foreign policy is determined by the West's international behavior – Moscow looking whether to emulate or to find alternatives to it; the present paper will compare Russia's legitimization arguments for the 2008 war and the 2014 annexation of Crimea trying to assess how Moscow answers Western criticism and whether there is a continuity in Russian official legitimization narratives.